Burden of Aortic Aneurysm and Its Attributable Risk Factors from 1990 to 2019: An Analysis of the Global Burden of Disease Study 2019 - Wang, Zhuo; You, Yayu; Yin, Zhehui; Bao, Qinyi; Lei, Shuxin; Yu, Jiaye; Xie, Cuiping; Ye, Feiming; Xie, Xiaojie (Frontiers in Cardiovascular Medicine, 2022)
Background: Global and national estimates on the epidemiology of aortic aneurysm are prerequisite for disease managing and policy making. Based on Global Burden of Disease (GBD) 2019, this study aimed to figure out the global aortic aneurysm burden by systematically analyzing demographic data of mortality and exploring the attributable risks and relevant factors. Methods：All data analyzed in this study were available in Global Health Data Exchange (GHDx) online query tool. The population in our study comprised individuals from 204 countries and territories from 1990 and 2019. The estimated annual percentage changes (EAPC), a common estimator using a linear regression model on the log of the age-standardized rates, was performed to assess age-standardized rates of deaths (ASRD) and disability-adjusted life-year (ASDALYR) and to predict temporal trends of aortic aneurysm. Spearman correlation analysis was performed to explore the relationship between burden of aortic aneurysm and covariates. Results: Though aortic aneurysm-related deaths and DALYs increased from 1990 to 2019, global ASRD and ASDALYR dramatically declined, both of which presented age dependence and gender differences. The global EAPC of ASRD and ASDALYR decreased, predicting gradual alleviation of disease burden. Smoking, high systolic blood pressure (SBP), diet high in sodium and lead exposure were the attributable risks of disease burden. Multiple factors were relevant to disease burden using Spearman correlation analysis Population-weighted mean temperature, age-standardized proportion of population living altitude, alcohol abstinence, smoking age of initiation, total physical activity per week, prevalence of Hepatitis and diabetes had negative correlation with ASRM and ASDALYR. However, age-standardized proportions of population living latitude, social asbestos consumption, educational attainment, healthcare access and quality index, alcohol consumption and smoking, intake of milk, red meats, poultry, polyunsaturated fatty acids vegetables, calcium, iron, zinc and vitamin A, prevalence of tuberculosis had positive correlation with ASRM and ASDALYR. Conclusions: In this study, decreasing trend of aortic aneurysm burden was found globally, especially in high SDI and high income region. These findings provide valuable insights to formulate increasingly integrated interventions to meet global vascular health challenge.